The woman in the purple skirt : a novel - Imamura, Natsuko, 1980- (Penguin Books, an imprint of Penguin Random House LLC, 2021)
"A bestselling, prizewinning novel of obsession and psychological intrigue about two enigmatic unmarried women, one of whom manipulates the other from afar, by one of Japan's most acclaimed young writers"--